FANGIRLING SEBAGAI PREDIKTOR KESEJAHTERAAN PSIKOLOGIS PADA WANITA KARIER PENGGUNA APLIKASI X - Caecillia Putri Nathasya Letto; Sutarto Wijono (Bajang Institute, 2025)
Fangirling is an emotional and cognitive involvement with idols that may influence an individual’s psychological condition. This study aims to examine the effect of fangirling on psychological well-being among career women who use application X. The participants consisted of 175 women aged 22–32 years, selected using purposive sampling technique. The instruments used were a fangirling scale developed based on McCutcheon’s theory and a psychological well-being scale adapted from Ryff. The results showed a significant effect between fangirling and psychological well-being, with a significance value of 0.000 < 0.05. This indicates that the higher the level of fangirling, the higher the psychological well-being among career women